A descriptive analysis of an outbreak of measles and a multilevel mixed-effects analysis of factors associated with case isolation in healthcare settings, London (February–June 2016). (June 2020) - Rana, S.; Saavedra-Campos, M.; Perkins, S.; Mohammed-Klein, R.; Wright, A.; Cordery, R.; Bell, A.; Heffernan, C.; Meltzer, M.; Begum, L.; Chow, Y.; Verlander, N.Q.; et al.
Abstract: Objectives: We described the epidemiology and healthcare exposures during a measles outbreak in London and identified factors associated with isolation on arrival to healthcare premises. Study design: We conducted a cohort study including all confirmed measles cases in London residents from February 1, 2016, to June 30, 2016, and semistructured interviews with two infection prevention and control teams (IPCTs). Methods: We described the outbreak and conducted a multilevel mixed-effects analysis to assess the relationship between sociodemographic and clinical factors and isolation on arrival to healthcare premises. We summarised the interviews. Results: There were 182 cases, mostly aged 17–35 years (46%; 84). Excluding cases younger than one year, 76% (92/120) were unvaccinated, including two healthcare workers. The majority presented with rash (97%; 174), and 42% (70/166) required hospitalisation. Of the recorded cases, 93% of cases (164/178) had visited a healthcare setting during their infectious period (median number of visits = 2). In 33% (59/178) of the visits, the case was isolated on arrival; when not isolated, four healthcare exposures resulted in further transmission. Presenting to the hospital as opposed to a general practitioner (GP) was associated with higher odds of isolation (odds ratio = 2.23, 95% confidence interval = 1.1–4.4) when adjusted for age, gender and presenting with a cough. The IPCT identified measles training using standardised risk assessments by triage nurses in accident and emergency and intelligence regarding measles activity in the community as positive measures to prevent healthcare exposures. Conclusions: We recommend opportunistic immunisation of unvaccinated young adults by GPs and that occupational health departments ensure their staff are protected against measles. Raising measles awareness in healthcare settings via training or regular sharing of current measles surveillance activity from public health to the IPCT and GP may improve triage and isolation of cases on arrival to healthcare premises. Highlights: Most of the cases were young unvaccinated adults, including healthcare workers. A third of the infectious cases were isolated on arrival to healthcare settings. We observed a high number of healthcare exposures. Cases attending accident and emergency services were more likely to be isolated. Despite high numbers of healthcare exposures, transmission was limited.